Kubla Khan : the emperor of everything - Krull, Kathleen; Byrd, Robert (New York : Scholastic, 2010)
An introduction to the thirteenth-century Chinese emperor which offers a more complete picture of the man than books which treat him as just a supporting player in Marco Polo's adventures.
Z
1080
Z
Keywords: Mongols -- Biography -- Juvenile literature; Mongols -- History -- Juvenile literature; Kings, queens, rulers, etc; Mongols -- Biography; Mongols -- History; Picture books for children